Maraknya Kriminalitas Di Kota Bandar Lampung (Studi Kasus Di Kec. Labuhan Ratu) - Dicko Ade Aryandhana; Muhammad Refky Mustofo; Jericho Aquila A.M (Jurnal Hukum dan Sosial Politik, 2023)
Research on crime in Bandar Lampung can make an important contribution to the development of government policy in dealing with crime. In addition, this research can also provide a clearer view of what types of crimes occur most frequently in this city and who is more vulnerable to becoming a victim of criminality. In this study, the researcher will use a qualitative approach by conducting in-depth interviews with various related parties such as security forces, the community, and crime victims. This research will try to identify the factors that cause the high crime rate in Bandar Lampung, such as social, economic, cultural, and environmental factors. The results show that the crime rate in Bandar Lampung is quite high. Based on the data obtained, the most common types of crime in the city are robbery, theft with violence, fraud, persecution, and narcotics. Therefore, understanding these types of crimes is important to help increase public awareness about the importance of keeping themselves and their property safe. The results show that crimes occur more frequently at night and in densely populated areas. Based on the results of the research conducted, it can be concluded that the crime rate in Bandar Lampung is quite high. The most common types of crime are violent crime and theft.